2014
DOI: 10.1371/journal.pntd.0002756
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium ulcerans Persistence at a Village Water Source of Buruli Ulcer Patients

Abstract: Buruli ulcer (BU), a neglected tropical disease of the skin and subcutaneous tissue, is caused by Mycobacterium ulcerans and is the third most common mycobacterial disease after tuberculosis and leprosy. While there is a strong association of the occurrence of the disease with stagnant or slow flowing water bodies, the exact mode of transmission of BU is not clear. M. ulcerans has emerged from the environmental fish pathogen M. marinum by acquisition of a virulence plasmid encoding the enzymes required for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 27 publications
3
69
1
Order By: Relevance
“…An indication for an aquatic niche environment was given in a recent longitudinal study reporting the persistence of M. ulcerans DNA in a village water site located in the BU endemic Mapé basin of Cameroon. Underwater detritus at a localized position of the water hole was repeatedly tested positive for M. ulcerans-specific DNA sequences over a period of more than 2 years after all local BU cases had been treated [45], suggesting that M. ulcerans has adapted to survive in a restricted niche environment. Several studies have indicated that M. ulcerans is unlikely to be free-living and may persist in the environment as a commensal, associated with another protective organism such as amoeboid protozoa or inhabitants of biofilms in stagnant water bodies [46][47][48].…”
Section: Environmental Reservoirsmentioning
confidence: 99%
See 2 more Smart Citations
“…An indication for an aquatic niche environment was given in a recent longitudinal study reporting the persistence of M. ulcerans DNA in a village water site located in the BU endemic Mapé basin of Cameroon. Underwater detritus at a localized position of the water hole was repeatedly tested positive for M. ulcerans-specific DNA sequences over a period of more than 2 years after all local BU cases had been treated [45], suggesting that M. ulcerans has adapted to survive in a restricted niche environment. Several studies have indicated that M. ulcerans is unlikely to be free-living and may persist in the environment as a commensal, associated with another protective organism such as amoeboid protozoa or inhabitants of biofilms in stagnant water bodies [46][47][48].…”
Section: Environmental Reservoirsmentioning
confidence: 99%
“…Furthermore, the anatomical site of the lesions was shown to vary with both age and gender. While children tend to have a more dispersed distribution of lesions over the body, lesions seem to become increasingly confined to the limbs in adults [32,45,54,57], presumably because children cover their trunks less often compared to adults. The gender difference varies between studies and is thought to be influenced by behavioral factors and environmental contact patterns.…”
Section: Potential Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, shedding of M. ulcerans from ulcerative lesions of humans with active BU disease may play a role in the dissemination of M. ulcerans in the African BU endemic regions. [14][15][16] Since recent studies indicated that M. ulcerans may persist for many months in underwater decaying organic matter, 112 it may be considered that infection occurs at contaminated water contact sites. Seroepidemiological studies in Ghana and Cameroon have shown that children are much earlier exposed to malaria parasites than to M. ulcerans, indicating that an involvement of insect vectors commonly found close to the households is highly unlikely.…”
Section: Hypotheses On the Mode(s) Of M Ulcerans Transmissionmentioning
confidence: 99%
“…4,5 The disease usually manifests itself as a painless nodule, a firm plaque, or an edematous lesion, which soon ulcerates with characteristic undermined edges.…”
Section: Introductionmentioning
confidence: 99%